Analisis Peran Kemampuan Kerja dan Pengawasan dalam Meningkatkan Produktivitas Pegawai Dinas - Muhammad Yalzamul Insan; Soulthan Saladin Batubara; Fandi Afriansa (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
The purpose of this study is to evaluate and improve our understanding of the impact of employability analysis and supervision on productivity. In this study, a quantitative methodology was used, and the sample size consisted of 85 people. Questionnaire dissemination is a method used to obtain data. The collected data was analyzed using statistical methods, especially using multiple regression analysis conducted with SPSS software. The results of the data analysis show that workability has a positive and significant influence on employee productivity. Employee performance is positively and significantly affected by supervision in a partial capacity. Because the value is greater than the value of the F table of 2.71, the F value of 69.916 is considered statistically significant at a significance level of 0.000. This level of significance is lower than the 0.05 criterion that is generally accepted in the scientific community. The ability to carry out work and supervise has a positive and significant influence on employee productivity in the workplace at the same time